2017
DOI: 10.1371/journal.pone.0185813
|View full text |Cite
|
Sign up to set email alerts
|

Serum high mobility group box 1 protein levels are not associated with either histological severity or treatment response in children and adults with nonalcoholic fatty liver disease

Abstract: AimSerum high mobility group box 1 protein (HMGB1) is a proinflammatory molecule that could potentially serve as a biomarker for non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) due to its correlation with degree of liver fibrosis. The aim of the current study was to examine the cross-sectional and longitudinal relationships between serum HMGB1 levels and liver histology in adults and children with NAFLD participating in two large randomized controlled trials.MethodsSerum HMGB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Despite that all these published data indicated extracellular HMGB1 may be detrimental in liver damage, there still exists controversy over the role of circulating HMGB1 plays in liver injury and its association with serum ALT. Although HMGB1 is found to be correlated with ALT activity during clinical acetaminophen hepatotoxicity (37), it is also reported that serum HMGB1 was not related to histological severity or serum ALT in adult and children NAFLD (38). In our mouse models, serum HMGB1 levels were signi cantly elevated by HFD from week 2, while ALT levels were not signi cantly different between HFD and LFD groups.…”
Section: Discussionmentioning
confidence: 51%
“…Despite that all these published data indicated extracellular HMGB1 may be detrimental in liver damage, there still exists controversy over the role of circulating HMGB1 plays in liver injury and its association with serum ALT. Although HMGB1 is found to be correlated with ALT activity during clinical acetaminophen hepatotoxicity (37), it is also reported that serum HMGB1 was not related to histological severity or serum ALT in adult and children NAFLD (38). In our mouse models, serum HMGB1 levels were signi cantly elevated by HFD from week 2, while ALT levels were not signi cantly different between HFD and LFD groups.…”
Section: Discussionmentioning
confidence: 51%
“…Despite that all these published data indicated extracellular HMGB1 may be detrimental in liver damage, there still exists controversy over the role of circulating HMGB1 plays in liver injury and its association with serum ALT. Although HMGB1 is found to be correlated with ALT activity during clinical acetaminophen hepatotoxicity (35), it is also reported that serum HMGB1 was not related to histological severity or serum ALT in adult and children NAFLD (36). In our mouse models, serum HMGB1 levels were signi cantly elevated by HFD from week 2, while ALT levels were not signi cantly different between HFD and LFD groups.…”
Section: Discussionmentioning
confidence: 51%
“…Despite that all these published data indicated extracellular HMGB1 may be detrimental in liver damage, there still exists controversy over the role of circulating HMGB1 plays in liver injury and its association with serum ALT. Although HMGB1 is found to be correlated with ALT activity during clinical acetaminophen hepatotoxicity (Antoine et al 2012 ), it is also reported that serum HMGB1 was not related to histological severity or serum ALT in adult and children NAFLD (Yates et al 2017 ). In our mouse models, serum HMGB1 levels were significantly elevated by HFD from week 2, while ALT levels were not significantly different between HFD and LFD groups.…”
Section: Discussionmentioning
confidence: 99%